ELECTROCHEMICAL BEHAVIOR AND ANALYSIS OF MONURON HERBICIDE IN WATER USING VOLTAMMETRIC METHODS AND PRE ACTIVATED CARBON PASTE ELECTRODE - Abdou, I.; Bouhidel, K. E. (Journal of Fundamental and Applied Sciences, 2018)
This research work dealt with the electrochemical behavior and voltammetric analysis of monuron, a phenyl urea herbicide. The sensitive enhancement of the monuron electrochemical signal, using a pre-activated carbon paste electrode, and the explanation of its mechanism were the main findings of this study. Unlike most used herbicides (linuron, diuron, fenuron, etc), monuron was rarely studied before by electrochemical methods. Indeed the square wave voltammetry allowed to optimize and to analyze monuron in water samples; the results showed two linear ranges of concentration: from 1.98 to 0.39 µg mL-1 and from 0.35 to 0.08 µg mL-1, with detection and quantification limits of LOD= 0.016 µg mL-1 and LOQ= 0.054µg mL-1 respectively. Besides these quantitative results, the anodic oxidation of monuron has been explained by an irreversible adsorption-controlled process, following a “one electron – one proton” mechanism.